2020
DOI: 10.1136/bmj.m2440
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium and health—concordance and controversy

Abstract: Nancy Cook and colleagues describe the sources of agreement and disagreement about the health effects of sodium and how they might be resolved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 55 publications
(65 reference statements)
3
50
0
Order By: Relevance
“…Reverse causation occurs when the likelihood of exposure is causally affected by the research outcome 50 . Persons with hypertension or other pre-existing illnesses (cardiovascular disease, kidney disease) may be advised to reduce sodium intake, and persons treated with diuretics or drugs that block RAAS provoking hyponatremia may have a lower apparent sodium intake 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Reverse causation occurs when the likelihood of exposure is causally affected by the research outcome 50 . Persons with hypertension or other pre-existing illnesses (cardiovascular disease, kidney disease) may be advised to reduce sodium intake, and persons treated with diuretics or drugs that block RAAS provoking hyponatremia may have a lower apparent sodium intake 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that modifiable lifestyle factors, such as nutrition and physical activity (PA), are closely linked to mental health ( Biddle et al, 2019 , Cook et al, 2020 ). In fact, several experts have expressed concerns about nutrition and PA when it comes to psychological burden during the COVID-19 pandemic ( Shen et al, 2020 ).…”
mentioning
confidence: 99%
“…Our analysis does not represent a direct assessment of the sodium–CVD risk relationship, a major issue of cardiovascular health and more generally human health. 135 137 However, the effect of sodium intake on BP is inherently of major interest, given the importance of BP to CVD morbidity and mortality, and the use of BP as a surrogate end point for CVD. 19 Therefore, the findings in this review and dose–response meta-analysis, confirming and strengthening previous reports and providing additional complementary information by summarizing the entire body of the evidence generated by human experimental studies, may provide sound evidence to strengthen recommendations to reduce dietary sodium intake in most populations and individuals.…”
Section: Discussionmentioning
confidence: 99%